ABEST21 International Accreditation Seminar 2024 - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
Impact Publishing Collaboration Session was a collaboration between researchers, institutions and universities in creating and publishing scientific works together. The main goal of this joint publication was to take advantage of the expertise, resources and networks of various parties so that the research results are more comprehensive and have a wider impact and are of better quality. Some key results of the Joint Publication activities were high-quality scholarly publications, increasing the number and reputation of publications, as well as expanding the academic network and reputation.